Efectuati :
a ) ( 2 + 2 x 3 ) x { 2 x 2^2 x 2^43 - 2^46 + [ 3^148 : 3^43 - ( 3^35 )^21 ] + 16 } ;
b ) 122 + 12 x { 183 : [ ( 2 x 2^3 x 5^3 )^4 : ( 2^4 x 3^7 x 5^12 ) + ( 2^8 )^9 : 2^72 - 1^27 x 5^0 ] - 9 x ( 54 - 2^4 x 3 ) ] } ;

1
la a ceva e gresit verifica
Comentariul a fost şters
Comentariul a fost şters
Comentariul a fost şters

Răspunsuri

2014-11-05T00:15:03+02:00
( 2 + 2 x 3 ) x { 2 x 2^2 x 2^43 - 2^46 + [ 3^148 : 3^43 - ( 3^5 )^21 ] + 16 }
8x{2
¹⁺²⁺⁴³-2⁴⁶+[3¹⁴⁸⁻⁴³-3¹⁰⁵]+16}=
8x{2⁴⁶-2⁴⁶+(3¹⁰⁵-3¹⁰⁵)+16}
=8x[0+0+16]=8x16=128
3 5 3